A framework with hybrid approach to analyse system requirements of smart PSS toward customer needs and co-creative value propositions. (January 2020) - Liu, Zhiwen; Ming, Xinguo; Qiu, Siqi; Qu, Yuanju; Zhang, Xianyu
Highlights: Smart product-service system has been characterized as value co-creation strategy. Conceptual factors can be composed of CNs, CVPs and SRs in terms of service logic. Two comparisons are conducted on coverage and evaluation of conceptual factors. A framework is proposed to capture three types of conceptual factors for smart PSS. A hybrid approach is employed to analyse SRs of smart PSS toward CNs and CVPs. Abstract: Smart product-service system (PSS) has been transcending scope of traditional PSS and can be characterized as value co-creation business strategy. This article aims to propose a framework with hybrid approach to capture and evaluate conceptual factors of smart PSS in fuzzy front end. According to service logic that is one of value co-creation paradigms, conceptual factors can be divided into customer needs (CNs) as customer problems to be solved, co-creative value propositions (CVPs) as mutual benefits and system requirements (SRs) as abstract solutions, which just match with three spheres of customer, joint and provider in service logic, respectively. Particularly, CVPs on smart PSS are captured from various interactions in its sequence diagram. As means-end chain theory, three types of conceptual factors for smart PSS are formed into multi-hierarchy network structure, and they are evaluated through a hybrid approach integrating fuzzy DEMATEL, modified-ANP and fuzzy TOPSIS. As a result, SRs prioritization is derived to give support to conceptual design of smart PSS. Sensitivity analysis also is conducted to test reliability of SRs prioritization. Finally, an illustrative case study of smart fridge-service system (SFSS) is demonstrated along this proposed methodological framework.